2019
DOI: 10.1074/jbc.ra118.006469
|View full text |Cite
|
Sign up to set email alerts
|

Methylation deficiency of chromatin proteins is a non-mutational and epigenetic-like trait in evolved lines of the archaeon Sulfolobus solfataricus

Abstract: Edited by John M. Denu Archaea are a distinct and deeply rooted lineage that harbor eukaryotic-like mechanisms, including several that manage chromosome function. In previous work, the thermoacidophilic crenarchaeon, Sulfolobus solfataricus, was subjected to adaptive laboratory evolution to produce three strains, called SARC, with a new heritable trait of super acid resistance. These strains acquired heritable conserved transcriptomes, yet one strain contained no mutations. Homologous recombination without all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 55 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…Prior work indicated that heritable hypomethylation of chromatin proteins and their binding to particular genes may mediate the SARC traits (10,12). However, these proteins bind the minor groove and their methylated residues are on solvent-facing surfaces (10) that do not appear to alter DNA-binding affinity (17,32). Therefore, it was predicted that the location and binding affinity of these proteins was invariant between wild type and SARC strains.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior work indicated that heritable hypomethylation of chromatin proteins and their binding to particular genes may mediate the SARC traits (10,12). However, these proteins bind the minor groove and their methylated residues are on solvent-facing surfaces (10) that do not appear to alter DNA-binding affinity (17,32). Therefore, it was predicted that the location and binding affinity of these proteins was invariant between wild type and SARC strains.…”
Section: Resultsmentioning
confidence: 99%
“…In eukaryotic histones, methylation changes on the solvent facing surfaces of histone cores do not alter DNA-binding affinity but can dramatically alter transcription and DNA repair through protein-protein interactions (23,37). Johnson et al found Cren7 and Sso7D were modified at solvent facing residues and not at DNA-contacting sites (10). Furthermore, methylation state does not alter DNA-binding affinity (17,32).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations